2017
DOI: 10.1016/j.neulet.2017.08.071
|View full text |Cite
|
Sign up to set email alerts
|

Grip force control and hand dexterity are impaired in individuals with diabetic peripheral neuropathy

Abstract: Diabetic peripheral neuropathy (DPN) affects the sensory function of the hands and, consequently, may negatively impact hand dexterity, maximum grip strength (GS), and hand grip force (GF) control during object manipulation. The aims of this study were to examine and compare the GF control during a simple holding task as well as GS and hand dexterity of individuals with DPN and healthy controls. Ten type 2 diabetic individuals diagnosed with DPN and ten age- and gender-matched healthy controls performed two tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
2
10
2
Order By: Relevance
“…While a previous meta-analysis showed hand grip strength, pinch strengths, and dexterity tended to be worse in patients with type 2 diabetes than in healthy people, differences were not statistically significant [20]. Hand grip strength were found not to differ between type 2 diabetes patients, with and without DPN, in a Brazilian population [21]. In contrast to this previous report, our study showed an association between weakened hand grip strength and DPN in a Japanese population.…”
Section: Discussioncontrasting
confidence: 99%
“…While a previous meta-analysis showed hand grip strength, pinch strengths, and dexterity tended to be worse in patients with type 2 diabetes than in healthy people, differences were not statistically significant [20]. Hand grip strength were found not to differ between type 2 diabetes patients, with and without DPN, in a Brazilian population [21]. In contrast to this previous report, our study showed an association between weakened hand grip strength and DPN in a Japanese population.…”
Section: Discussioncontrasting
confidence: 99%
“…Diabetic neuropathy (DN) is one of the most common diabetic complications and is characterized by complex changes in functional and sensorimotor parameters (2). The pathophysiology of DN involves a complex cascade of specific interrelated mechanisms (3,4). Oxidative stress is an important contributor to the development of DN; this is due to the dramatic increase in the level of free radicals generated in patients with diabetes (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Since 1988, the test is used as an upper limb outcome measurement in multiple sclerosis, a disease with an involvement of the corticospinal tract [6]. In the last years, the NHPT could be assessed as a reliable test for dexterity in other diseases of the central nervous system such as stroke [7], traumatic brain injury [8], and cerebral palsy [9] but also for diseases with an involvement of the lower motor neurons as peripheral neuropathies [10, 11]. Transcranial magnetic stimulation (TMS) with resting-motor threshold (RMT) is a tool to show the involvement of the UMNs.…”
Section: Introductionmentioning
confidence: 99%